Analysis of News Translation Strategy on Muhammadiyah University Website: Qualitative Study Based on Bielsa and Bassnett's Theory - Violyn, Cherish Mauretha Mahar; Maghfiroh, Ana; Mustikawati, Diyah Atiek; Indriastuti, Niken Reti; Asiyah, Siti (Jurnal Keilmuan dan Keislaman, 2024)
Translation plays a crucial role in global communication and education. This research examined the translation strategies used to translate Indonesian news from the official websites of the top three Muhammadiyah universities into English. The objectives of this study were: 1) to identify the translation strategies employed in translating online news from Indonesian to English on the official websites of the top three Muhammadiyah universities, 2) to describe the application of these translation strategies in the Indonesian-to-English online news translations, and 3) to investigate the impact of bilingual or multilingual online news on the websites of the top three Muhammadiyah universities. The researcher employed a qualitative content analysis method. Data were collected from 30 news articles published in Bahasa Indonesia, along with their English translations, with 10 articles sourced from each of the top three Muhammadiyah universities' websites. The analysis and categorization were conducted based on the news translation theory proposed by Bielsa and Bassnett. Additionally, website analysis was used to assess the impact of bilingual news on the universities' websites. The results revealed that the most commonly used translation strategies were elimination (41.25%) and addition (21.88%). Furthermore, having a bilingual university website could attract foreign visitors, as the availability of information in multiple languages or formats positively influences webometrics rankings by increasing the diversity of visitors.